Entry and Exit, Multi-Product Firms, and Allocative Distortions - Fattal Jaef, Roberto N. (World Bank, Washington, DC, 2017)
This paper proposes a multi-product model of firm dynamics to understand the implications of allocative distortions for the decisions of firms to enter, exit, and supply products to the market. These margins of adjustment have been largely neglected in the literature yet have direct contributions to welfare and productivity. The paper finds that when the analysis accounts for these channels, the traditional focus on long-run gains in Total Factor Productivity from reversing misallocation strongly underestimates the welfare gains that accrue when accounting for transitional dynamics. Calibrating the distortions to China in 1998, the analysis finds a welfare gain of 32 percent and a steady-state gain of 10 percent.